Mitochondrial quality orchestrates muscle-adipose dialog to alleviate dietary obesity. (March 2019) - Xu, Zhisheng; Fu, Tingting; Guo, Qiqi; Sun, Wanping; Gan, Zhenji
Graphical abstract: Abstract: Skeletal muscle fitness is vital for human health and disease and is determined by the capacity for burning fuel, mitochondrial ATP production, and contraction. High quality mitochondria in skeletal muscle are essential for maintaining energy homeostasis in response to a myriad of physiologic or pathophysiological stresses. A sophisticated mitochondrial quality control system including mitochondrial autophagy, dynamics, and proteolysis has been identified, which maintains their functional integrity. In this review, we discuss recent studies highlighting mitochondrial quality control mechanisms that govern systemic metabolism by skeletal muscles. Increasing evidence suggests that mitochondria can "communicate" with the nucleus and triggers adaptive genomic re-programming during stress response. We focus on participation of the mitochondrial quality control system in the regulation of mitochondrial communications that drive the muscle to adipose dialog and suggest that muscle-specific regulation of mitochondrial quality impacts systemic homeostasis.